Associations of combined exposure to selected metal mixtures with thyroid hormones in children: a cross-sectional study in China - Cao, Yuhan; Xiang, Shiting; Du, Yuwei; Chen, Meiling; Xue, Rumeng; Li, Qi; Qiu, Jun; Duan, Yanying (Frontiers in Public Health, 2025)
BackgroundExposure to several metal elements has been found to be associated with thyroid hormone homeostasis. However, evidence for combined exposure is inconclusive, especially for children.ObjectiveTo examine the individual and joint effects of blood metal elements on thyroid hormones in children.MethodsA total of 12,470 children aged 0–14 were collected from January 2018 to December 2021 in Hunan Children's Hospital. The concentrations of lead (Pb), iron (Fe), calcium (Ca), copper (Cu), zinc (Zn) and magnesium (Mg) in blood were detected via atomic absorption spectrometry (AAS). The levels of thyroid stimulating hormone (TSH), triiodothyronine (TT3, FT3) and total and free thyroxine (TT4, FT4) were measured by electrochemiluminescence immunoassay (ECLIA). Generalized linear regression (GLR) model and Quantile-based g-computation (QGC) were employed to estimate the association between metal exposure and thyroid hormone homeostasis.ResultsGLR model showed that a unit increase in ln-transformed Fe was associated with increases in TT3 (β = 0.163; PFDR < 0.001), TT4 (β = 12.255; PFDR < 0.001) and FT3 (β = 0.615; PFDR < 0.001), as well as decreases in TSH (β = −0.471; PFDR = 0.005) and FT4 (β = −1.938; PFDR < 0.001). The result of QGC analysis indicated a positive relationship of the ln-transformed concentration of metal mixture with the levels of TT3 (β = 0.018; P = 0.012), TT4 (β = 2.251; P < 0.001) and FT3 (β = 0.074; P < 0.001) in children. Fe was the predominant contributor among the metal mixture with positive contributions to TT3 (weight = 0.439), TT4 (weight = 0.502) and FT3 (weight = 0.450).ConclusionsThe combined metal exposure was associated with increased levels of TT3, TT4, and FT3 in children and Fe appeared to be the major contributor. Further studies are warranted to confirm our findings and elucidate the underlying mechanisms.